SCF (Fbxl17) ubiquitylation of Sufu regulates Hedgehog signaling and medulloblastoma development - D'Angiolella, V; Raducu, M; Fung, E; Sebastien, S; Infante, P; Alessandro, B; Fischer, R; Bristow, C; Marie-Laetitia, T; Finta, C; Christianson, J; Francesca, B; et al. (EMBO Press, 2016)
SCF (Skp1-Cul1-F-box protein) ubiquitin ligases direct cell survival decisions by controlling protein ubiquitylation and degradation. Sufu (Suppressor of fused) is a central regulator of Hh (Hedgehog) signaling and acts as a tumour suppressor by maintaining the Gli (Glioma-associated oncogene homolog) transcription factors inactive. Although Sufu has a pivotal role in Hh signaling, the players involved in controlling Sufu levels and their role in tumour growth are unknown. Here, we show that Fbxl17 (F-box and leucine-rich repeat protein 17) targets Sufu for proteolysis in the nucleus. The ubiquitylation of Sufu, mediated by Fbxl17, allows release of Gli1 from Sufu for proper Hh signal transduction. Depletion of Fbxl17 leads to defective Hh signaling associated with impaired cancer cell proliferation and medulloblastoma tumour growth. Furthermore, we identify a mutation in Sufu, occurring in medulloblastoma of patients with Gorlin syndrome, that increases Sufu turnover through Fbxl17-mediated polyubiquitylation and leads to sustained Hh signaling activation. In summary, our findings reveal Fbxl17 as a novel regulator of Hh pathway and highlight perturbation of the Fbxl17-Sufu axis in the pathogenesis of medulloblastoma.